2010
DOI: 10.1002/mde.1523
|View full text |Cite
|
Sign up to set email alerts
|

Spatial aspects of ticket scalping

Abstract: We develop a simple insurance model of the secondary market for tickets to account for some of the observed spatial patterns of prices. Beyond ticket markets the model draws attention to the existence of subtle insurance fees in market prices that may be incorrectly attributed to breakdown of the law of one price or attributed solely to a cost-based rationale. Copyright (C) 2010 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Thus, it's unlikely that ticket re-sales have a substantial impact on our results. Similarly, it is unlikely that issues related to resellers (e.g., 'scalpers') as addressed in Karp and Perloff (2005) or Goff and Tollison (2011) are relevant for our analysis.…”
Section: Evaluating Assumptionsmentioning
confidence: 99%
“…Thus, it's unlikely that ticket re-sales have a substantial impact on our results. Similarly, it is unlikely that issues related to resellers (e.g., 'scalpers') as addressed in Karp and Perloff (2005) or Goff and Tollison (2011) are relevant for our analysis.…”
Section: Evaluating Assumptionsmentioning
confidence: 99%
“…In the literature of gray markets and second-hand markets, the goods studied are generally durables whereby advance selling is hardly practiced (Anderson and Ginsburgh 1994, Rao et al 2009, Yin et al 2010. However, in the literature of ticket scalping (Goff andTollison 2011, Karp andPerloff 2005), it was shown that a perishable-good monopoly that can charge different prices in different periods but cannot price discriminate within a period may benefit from the existence of a resale market.…”
Section: Introductionmentioning
confidence: 99%
“…2010). However, in the literature of ticket scalping (Goff and Tollison 2011, Karp and Perloff 2005), it was shown that a perishable‐good monopoly that can charge different prices in different periods but cannot price discriminate within a period may benefit from the existence of a resale market.…”
Section: Introductionmentioning
confidence: 99%